Puesta En Funcionamiento De La Máquina Emco Compact 5 CNC De La Universidad Antonio Nariño, Sede Bogotá sur (2023)
In this project, the CNC Compact 5 lathe was commissioned, from the Antonio Nariño University, Bogotá south, which was in a state of abandonment and out of service, so it was not providing any function to the educational community. Throughout this document, the different objectives and results obtained to technologically update and put the CNC lathe into operation were carried out and evaluated, within the objectives: a diagnosis of the machine in order to determine the interventions to be executed, the mechanical and electrical design with the respective mechanical plans and electrical diagrams, implementing the different elements in the machine, and finally an operation and maintenance manual was made with a practical guide, leaving the machine in service, for students of the different subjects and degree projects related to machining and manufacturing of parts.